‘Everyone knows everyone’: youth perceptions of relationships and sexuality education, condom access and health services in a rural town - Heslop, C.; Burns, Sharyn; Lobo, R. (Routledge, 2019)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. Sexual health promotion and Relationships and Sexuality Education (RSE) are influenced by interrelated social and cultural factors, particularly in a rural setting. This paper reports on findings from interviews with young people when asked about experiences and perspectives accessing RSE and sexual health services in a small rural Australian town. Fifteen young people (16–24 years) participated in semi-structured focus groups and interviews. Data was analysed and coded with four key themes emerging: relevant and credible sexual health education; make it easy; GP accessibility; and discreet condom supply. The findings of this study have practical implications when addressing community level sexual health and RSE needs.